Cognitive motor dual tasking as a game-changer in basketball training programs: a new approach to developing elite basketball players - Shalom, A.; Gottlieb, R.; Conte, D.; Calleja-Gonzalez, J. (Frontiers in Psychology, 2025)
In basketball, as an open-skill sport, coordinating physical, technical, and mental components is a key challenge in the training process (Shalom et al., 2023; Zhang et al., 2025). A deep understanding of the game's specific demands, combined with physiological and biomechanical analyses of movement, is essential for the accurate planning of team training programs (Sosa et al., 2025). Such understanding enables the making of informed decisions when selecting appropriate training methods, ensuring targeted preparation for both practices and competitions, integrating advanced technologies, and designing tailored exercises using specialized equipment (Gottlieb et al., 2021; Marocolo and Souza, 2024). Although the past decade has seen significant progress in the integration of physical and cognitive components, along with the implementation of advanced technologies in elite sports, when considering basketball training programs, a substantial gap remains between the strong focus on physical training and the limited attention given to specific, on-court cognitive training (Fuster et al., 2025). This is despite the growing recognition of the importance of integrating both the physical and cognitive demands of the modern game (Zhang et al., 2025). Indeed, basketball requires rapid decision-making and, real-time adaptations to changing situations, and immediate responses to continuous pressure from various factors such as opponents and environmental (e.g., crowd noise) and variable playing conditions (Lucia et al., 2021; Shalom et al., 2025).